Religiosity Behind Bars: A Study on Guilt in Class IIA Martapura Women's Correctional Facility - Sapitri, Nurlita; Ariani, Lita (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2023)
The development and progress of the world with various kinds of actions or human behavior. Negative actions that can harm themselves and others that can cause guilt often occur in fostered citizens. Built residents who feel guilty will cause regret in themselves for harming others, so there is a desire to make changes for the better by studying religion. This study aims to determine the effect of religiosity on guilt in built residents at the Martapura Class IIA Women's Correctional Institution using two variables. This research method uses a quantitative approach with a correlational type of research. Sampling in this study used probability sampling techniques with random sampling methods. This study involved 213 built residents in Martapura Class IIA Women's Correctional Institution. The measuring instruments used in this study were the scale of religiosity and the scale of guilt using the Likert scale model. Through the results of this study, there is an influence of religiosity on guilt in built residents at the Martapura Class IIA Women's Correctional Institution with the results of the calculated F value is 99.254 with a significance level of .000< 0.05 and the value of the coefficient of determination / R Square is obtained at 0.320 which means the influence of religiosity on guilt is 32%.